The effect of different growing medium combination on growth and yield of Boesenbergia rotunda - Md Nasir, Nasiroh; Shahari, Rozilawati; Tajudin, Nur Shuhada (Sciendo, 2020)
Boesenbergia rotunda or Temu kunci is a herb belonging to the Zingiberaceae family and wildly cultivated in Malaysia by rhizome. Temu kunci rhizome is commonly used in traditional medicines to cure stomach aches, promote appetite and gout. Due to its potential to be developed as one of Malaysia’s herbal products, information on their agronomic requirements is needed. This study was conducted to investigate the effects of the different combination of the growing medium on B. rotunda growth and yield. Topsoil, peat moss, sand and chicken manure with four different ratios have been used as a planting medium. The potted plant was arranged in a randomised, complete block design with five replicates. The growth parameter was measured during harvesting time. The results showed that there was no significant difference in plant height, number of leaves, tiller number, fresh and dry shoot weight and fresh and dry root and rhizome weight in all treatments. It can be argued that this is because B. rotunda can be grown in different kinds of planting medium. Based on this study, it was suggested that topsoil be used for Temu Kunci planting, since it is easily obtained and requires less money.